Allergen-associated molecular patterns: a new trend in modern allergology - V. S. Sviridova; P. Yu. Isaev; V. V. Klimov; M. I. Romanova; N. S. Koshkarova (Бюллетень сибирской медицины)
Over the last decade the role of innate immunity has been known to be crucial for the activation of adaptive immune system. The main triggers that upregulate reactions of innate immunity are small exogenous molecules with conserved motifs, molecular patterns. The article discusses a variety of possible roles of molecular patterns in the immune mechanisms, including the participation of Allergen Associated Molecular Patterns (AAMPs) in allergic processes.